Technologies for arsenic removal from drinking water : a compilation of papers presented at the International Workshop on Technologies for Arsenic Removal from Drinking Water organized by Bangladesh University of Engineering and Technology (BUET), Dhaka, Bangladesh and the United Nations University (UNU), Tokyo, Japan - International Workshop on Technologies for Arsenic Removal from Drinking Water (2001 : Dhaka, Bangladesh); Ahmed, M. Feroze; Ali, M. Ashraf, 1965-; Adeel, Zafar; Bangladesh University of Engineering and Technology; United Nations University (Dhaka : Bangladesh University of Engineering and Technology ; Tokyo : United Nations University, 2001)
Includes some papers with reference to Bangladesh and India.
Includes bibliographical references.
LIB
Keywords: Water -- Purification -- Arsenic removal -- Bangladesh -- Congresses; Water -- Purification -- Arsenic removal -- India -- Congresses